New Pd(II) schiff base complexes derived from ortho-vanillin and l-tyrosine or l-glutamic acid: Synthesis, characterization, crystal structures and biological properties. (1st September 2018) - Muche, Simon; Harms, Klaus; Biernasiuk, Anna; Malm, Anna; Popiołek, Łukasz; Hordyjewska, Anna; Olszewska, Anna; Hołyńska, Małgorzata
Graphical abstract: Four new Pd(II) complexes with the ligands derived from ortho -vanillin and either l -glutamic acid or l -tyrosine and their properties are presented. Abstract: Four new Pd(II) complexes are presented, [Pd(L1)(Cl)]K (1 ), [Pd(L1)(Cl)]Na (2 ), [Pd(L2)(Cl)]Na (3 ) and [Pd(L2)(H2 O)] (4 ), where the ligands are derived from ortho -vanillin and either l -glutamic acid (L1 ) or l -tyrosine (L2 ). The complexes were characterized by X-ray diffraction studies, ESI-MS, IR and NMR spectroscopy and elemental analysis. Complexes 1, 2 and 4 were found to be stable on dissolution in DMSO over 72 h. Complex 3 underwent decomposition and rearrangement and the available NMR results point to an equilibrium with 4 in solution. Investigation of bioactivity for the complexes and the ligand L2 revealed moderate to good antimicrobial activity of the complexes, whereas the ligand was inactive. In cytotoxicity studies with L929 cells all compounds displayed no cytotoxic properties up to a concentration of 200 µM.